Dispersion of Leishmania (Leishmania) infantum in central-southern Brazil: Evidence from an integrative approach - Pasquali, Aline Kuhn Sbruzzi (PLoS Negl Trop Dis, 2019)
Leishmania (Leishmania) infantum is the zoonotic agent of visceral leishmaniasis (VL), a disease with a global distribution. The transmission scenario of VL has been undergoing changes worldwide, with the biologic cycle invading urbanized areas and dispersing the parasites into other previously free areas. The epidemiological cycle in Brazil has dispersed from the Northeast to other regions of the country. In this study, an integrative approach, including genotyping Brazilian strains of L. (L.) infantum for 14 microsatellite markers and reviewing historical records of the disease, was used to assess dispersion routes throughout central-southern Brazil. Our results support three L. (L.) infantum dispersion routes: A) dispersion from Bolivia to the states of Mato Grosso, Mato Grosso do Sul and São Paulo via the Bolivia-Brazil gas pipeline from 1998 to 2005; B) VL dispersion from Paraguay to the Brazilian side of the triple border (Foz do Iguaçu and Santa Terezinha de Itaipu) during after 2012; and C) emergence of a new L. (L.) infantum cluster in western Santa Catarina State and its dispersion to southern Paraná State (municipality of Pato Branco), after 2013. Hypotheses regarding possible entries of Leishmania (L.) infantum into the area of the triple border are presented and discussed. Understanding how VL has dispersed is vital to the development of control measures for this disease and to avoid future dispersion events.